Rich Language Learning Environment and Young Learners’ Literacy Skills in English - Luh Putu Artini (Bina Nusantara University, 2017)
This research aimed at developing rich language learning environment to help elementary school students develop their literacy skills in English. Shortage of professional English teachers in primary school, limited time allocation, as well as the lack of tools and facilities that support English language teaching and learning for young learners had resulted in students’ low literacy skills in English. It was tried out in six primary schools across Bali involving 12 teachers and 520 students. The data were collected through questionnaires, observation, interview, English literacy tests, and students’ literacy journals. Research finds that young learners should have the opportunity to learn by doing without too much intervention so that a natural process of learning could occur. The product comprises multiple literacy experiences in the form of five different texts. The findings reveal that the readability of the material is in the category of high. The systematic exposures of these materials to beginner learners of English have been proven to have the significant impact on their literacy skills. The highest improvement is found in word level (87,1%), followed by sentence level (56,2%), and discourse level (46,8%). The improvements are all confirmed at the significance level of 0,05. The research also finds that RLLE has the positive impact on the development of self-directed learning skills.